Mortality Benefit of Alirocumab: A Bayesian Perspective. Issue 20 (15th October 2019) - Labos, Christopher; Brophy, James M.; Sniderman, Allan; Thanassoulis, George
Abstract : Background: The ODYSSEY OUTCOMES (Alirocumab and Cardiovascular Outcomes after Acute Coronary Syndrome) trial demonstrated that alirocumab reduced major cardiovascular events. However, because of the hierarchical testing strategy used for the multiple outcomes examined, the observed reduction in all‐cause mortality was labeled "nominally significant" which has clouded its interpretation. Methods and Results: We re‐analyzed data from ODYSSEY OUTCOMES using Bayesian methods and generated various prior probabilities by incorporating mortality data from previous similar PCSK9 (proprotein convertase subtilisin‐kexin type 9) inhibitor trials. We first used data from the ODYSSEY OUTCOMES trial with a non‐informative prior, then sequentially added data from ODYSSEY LONG TERM and the FOURIER trial, giving FOURIER full weight, 50% weight and 10%. The posterior probability of a mortality reduction using only the ODYSSEY OUTCOMES data was hazard ratio 0.85 (95% CI 0.74–0.99) which corresponded to a 98.4% probability of a mortality benefit. When the ODYSSEY LONG TERM data were added to the analysis, the posterior probability was hazard ratio 0.84 (95% CI 0.72–0.97) with a 99.9% probability of mortality reduction, and when the FOURIER data were added to the analysis the posterior probability was hazard ratio 0.94 (95% CI 0.85–1.04) with an 89.1% probability of a mortality reduction. When the FOURIER trial was given only 50% or 10% weight, the probability of a mortality reduction rose 95.4% and 98.7%, respectively. We estimate that the probability of >1% absolute risk reduction ranges from 8% to 24%, while the probability of >0.5% absolute risk reduction ranges from 66% to 89%. Conclusions: Our analysis demonstrates a high likelihood that alirocumab confers a reduction in all‐cause mortality, despite the equivocal interpretation of the data in the original ODYSSEY OUTCOMES publication.